Sea fish fraud? A confirmation of Gadoid species food labelling. Issue 1 (3rd January 2017) - Kyrova, Veronika; Surmanova, Pavla; Ostry, Vladimir; Rehurkova, Irena; Ruprich, Jiri; Jechova, Marie
Abstract : Purpose: Gadoid fish and hake are the species of fishes most frequently imported to the Czech Republic. The purpose of this paper, cross-country hygiene study, is to determine sea fish fraud labelling on the Czech market and catering. Design/methodology/approach: In total, 57 samples of commercial Gadoid fish product from different manufacturers, distributors and catering facilities were gathered. Gadidae family, hake ( Merluccius spp. Raf.), saithe ( Pollachius virens L.), Atlantic cod ( Gadus morhua L.), Alaska pollock ( Theragra chalcogramma Pall.), were detected in fish meat, fish products and fish meals by the qualitative PCR method. Findings: In total, 47 samples were labelled as a Gadoid fish, which were confirmed in 43 cases. Six samples were labelled as a hake and were confirmed in five samples. Four samples were labelled as a fish fillets. Three samples of fish fillets were identified as a hake and one sample was detected as a mixture of Alaska pollock and Atlantic cod. Social implications: In recent years, due to increasing interest from consumers in the sea fish meat market, accurate Identification of fish species has become more important. The mislabelling of sea fish species, whether intentional or not, was on observed on the Czech market and in catering facilities. Economic factors influence the accuracy of labelling of fish meat, which is a concern as mislabelling can threaten public health. Originality/value: The study was concentrated on the monitoring of hygiene and quality of food products and catering facilities. This study provides greater awareness of the condition and quality of food on the market and to the extent of fraudulent practices amongst dealers and producers.